Selective inhibition of soluble tumor necrosis factor signaling reduces abdominal aortic aneurysm progression - Griepke, Silke; Grupe, Emilie; Lindholt, Jes Sanddal; Fuglsang, Elizabeth Hvitfeldt; Steffensen, Lasse Bach; Beck, Hans Christian; Larsen, Mia Dupont; Bang-Møller, Sissel Karoline; Overgaard, Martin; Rasmussen, Lars Melholt; Lambertsen, Kate Lykke; Stubbe, Jane (Frontiers in Cardiovascular Medicine, 2022)
Background Tumor necrosis factor (TNF) is pathologically elevated in human abdominal aortic aneurysms (AAA). Non-selective TNF inhibition-based therapeutics are approved for human use but have been linked to several side effects. Compounds that target the proinflammatory soluble form of TNF (solTNF) but preserve the immunomodulatory capabilities of the transmembrane form of TNF (tmTNF) may prevent these side effects. We hypothesize that inhibition of solTNF signaling prevents AAA expansion. Methods The effect of the selective solTNF inhibitor, XPro1595, and the non-selective TNF inhibitor, Etanercept (ETN) was examined in porcine pancreatic elastase (PPE) induced AAA mice, and findings with XPro1595 was confirmed in angiotensin II (ANGII) induced AAA in hyperlipidemic apolipoprotein E (Apoe) –/– mice. Results XPro1595 treatment significantly reduced AAA expansion in both models, and a similar trend (p = 0.06) was observed in PPE-induced AAA in ETN-treated mice. In the PPE aneurysm wall, XPro1595 improved elastin integrity scores. In aneurysms, mean TNFR1 levels reduced non-significantly (p = 0.07) by 50% after TNF inhibition, but the histological location in murine AAAs was unaffected and similar to that in human AAAs. Semi-quantification of infiltrating leucocytes, macrophages, T-cells, and neutrophils in the aneurysm wall were unaffected by TNF inhibition. XPro1595 increased systemic TNF levels, while ETN increased systemic IL-10 levels. In ANGII-induced AAA mice, XPro1595 increased systemic TNF and IL-5 levels. In early AAA development, proteomic analyses revealed that XPro1595 significantly upregulated ontology terms including “platelet aggregation” and “coagulation” related to the fibrinogen complex, from which several proteins were among the top regulated proteins. Downregulated ontology terms were associated with metabolic processes. Conclusion In conclusion, selective inhibition of solTNF signaling reduced aneurysm expansion in mice, supporting its potential as an attractive treatment option for AAA patients.